Performance of MR-Deduster on particulate emission control for a different area of axial entry - Mohd. Yusof, Mohd. Rashid (2013)
Multi-cyclones are widely used as industrial gas-cleaning device in controlling particulate emission from many stationary sources. However, understanding on the operation of multicyclones is hardly available in literatures. In this respect, a study to investigate the effect of different area of axial entry of a miniature cyclone of MR-deDuster, a multi-cyclones unit developed as particulate emission control device is presented in this paper. The development of the MR-deDuster was based on semi-empirical equations introduced by Lapple coupled with standard cyclone dimensions by Stairmand. In addition, the MR-deDuster was based on some assumptions and its performance was examined based on the actual particulate emission data collected from an incineration plant. Based on the predictions, the results showed that a greater amount of finer particulates size fraction was obtained using a miniature cyclone with smaller area of axial entry. However, the problems of having too many miniature cyclones with smaller area of axial entry must be taken into consideration in actual plant application. A detailed illustration on the performance of the MR-deDuster is discussed further in this paper.